2014
DOI: 10.1371/journal.pone.0101105
|View full text |Cite
|
Sign up to set email alerts
|

Trait Aggressiveness Is Not Related to Structural Connectivity between Orbitofrontal Cortex and Amygdala

Abstract: Studies in both pathological and healthy samples have suggested altered functional connectivity between orbitofrontal cortex (OFC) and amygdala as a possible cause of anger and aggression. In patient populations presenting with pathological aggression, there is also evidence for changes in structural connectivity between OFC and amygdala. In healthy samples, however, the relationship between white matter integrity and aggression has not been studied to date. Here, we investigated the relationship between trait… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 27 publications
0
15
0
Order By: Relevance
“…No differences in FA values along the UF were found in the current study. In a previous study in healthy individuals, no link was found between UF microstructure and trait aggressiveness (Beyer et al 2014). Furthermore, in a study with IED patients, no differences in white matter in brain areas corresponding to the UF were found as well (Lee et al 2016).…”
Section: Discussionmentioning
confidence: 68%
“…No differences in FA values along the UF were found in the current study. In a previous study in healthy individuals, no link was found between UF microstructure and trait aggressiveness (Beyer et al 2014). Furthermore, in a study with IED patients, no differences in white matter in brain areas corresponding to the UF were found as well (Lee et al 2016).…”
Section: Discussionmentioning
confidence: 68%
“…There seems to be a tendency for associations between trait measures and abnormal white matter structure to be found in clinical populations rather than in healthy controls. For example, Beyer et al (2014) did not find an association between trait anger or physical aggressiveness and FA in bilateral uncinate in healthy participants. In contrast, deficits in structural prefrontal-amygdala connectivity were identified in criminal offenders with psychopathy and adolescents and adults with conduct disorder.…”
Section: Discussionmentioning
confidence: 72%
“…An important question for future studies is to what extent altered amygdala-PFC connectivity is structural or neuromodulatory. In a recent study of a large cohort of healthy male participants (N = 93), Beyer et al 55 did not observe a significant difference in a measure of structural connectivity between the amygdala and PFC in those with high compared to low traitaggressiveness. It will be essential to extend such studies to clinical/pathological manifestations of aggression, however.…”
Section: Prefrontal Cortex and Prefrontal-amygdala Interactionsmentioning
confidence: 92%